2007
DOI: 10.1021/ac062002t
|View full text |Cite
|
Sign up to set email alerts
|

Calculating Optimal Modulation Periods to Maximize the Peak Capacity in Two-Dimensional HPLC

Abstract: Theoretical calculations are presented to optimize modulation period for maximum total peak capacity in comprehensive two-dimensional HPLC (2D-HPLC) taking into account the effect of modulation on the apparent peak capacity of the first-dimension (1D) separation. Results indicate that modulation periods are most favorable when they are adjusted to approximately 2.2-4 times the standard deviation of a 1D peak in order to avoid excessively short run times at the second dimension (2D). Data are presented that eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
81
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(89 citation statements)
references
References 32 publications
7
81
1
Order By: Relevance
“…Parameters recommended in refs. [2,3,5,6] corresponded to the lowest acceptable (rather than optimal) sampling densities due to unpredictable harm at much lower densities. Recommended parameters based on the experimental data for LC6LC [2,6] with its incompressible mobile phase could be compared with optimal parameters found here for GC6GC with small gas decompression in the second-dimension column.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Parameters recommended in refs. [2,3,5,6] corresponded to the lowest acceptable (rather than optimal) sampling densities due to unpredictable harm at much lower densities. Recommended parameters based on the experimental data for LC6LC [2,6] with its incompressible mobile phase could be compared with optimal parameters found here for GC6GC with small gas decompression in the second-dimension column.…”
Section: Discussionmentioning
confidence: 95%
“…Sampling periods recommended for accumulating [2,6] and snapshot [3,5] resampling are known from several reports where they were obtained from computer simulations of Gaussian peaks. In most cases, the simulations were complimented by the experimental data [2,5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a later study by Horie and co-workers [113], it was shown that the best compromise between sampling rate and second dimension analysis time in on-line LC×LC can be achieved when each first dimension peak is sampled a minimum of two times. The reason for this is that, while increased sampling rates are required to maintain first dimension resolution, the use of shorter second dimension analyses comes with a reduction in peak capacity in this dimension, ultimately lowering the overall peak capacity.…”
Section: Peak Capacity Sampling Frequency and Orthogonalitymentioning
confidence: 99%
“…Tanaka et al (Horie et al, 2007) showed that the sampling time applied for the second dimension ( 2 D separation) should be adjusted to 2-4 times the standard deviation of the firstdimension ( 1 D separation) peak (i.e., one or two 'cuts' per 1 D peak). This yields the best compromise between the time available for the 2 D separations and maintaining separation obtained in the first dimension (Eeltink et al, 2009).…”
Section: Liquid Chromatographymentioning
confidence: 99%